(untitled) (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2013)
Transinformação Vol. 24, n. 2 (2012) Link de acesso ao número http://periodicos.puc-campinas.edu.br/seer/index.php/transinfo/issue/view/128